Delivery and assessment techniques for the subject "integrated design" in civil engineering - Alengaram, Ubagaram Johnson; Hashim, Roslan; Lai, Sai Hin (2014)
New subjects are being introduced in Engineering on combining various issues that need immediate attention; recently, many universities introduced the subject known as Integrated Design for Civil Engineering stud~ts as a final year core course. The objective of this course to developing students' mind-set to understand the Vital issue on sustainability; further integrating various aspects of design in civil engineering and infuse leadership & teamwork capabilities. This subject is quite different from other core subjects as every student is expected to conceive the conceptual design and develop the concept into a project through design by working in a group; the group is also expected to develop the whole project by addressing the sustainable issues in their project. Though it is group work based project, in addition to group assessment, evaluating every student on their achievement of the course outcome is mandatory to understand the students' capability. The academic staffs faces a difficult task in evaluating individuals and group on the conceptual design, design elements, sustainability issues, communication skill, team work, leadership capability, etc. As we started the course four years back, we adapted a methodology in evaluating the students on assessing various components of the subject. Over these years, we have modified the delivery and assessment technique and it proved to be effective in both the delivery of the subject and in assessment of the students both as an individual and group.